On the Nexus Between CSR Practices, ESG Performance, and Asymmetric information - Berto Usman; Oscar Tiago Fontes Bernardes; Paulus Sulluk Kananlua (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2020)
The purpose of this paper is to test the relationship of CSR practice–asymmetry information and ESG performance–asymmetry information. We conjecture that there might be a particular role where the disclosure of non-financial information is deemed useful in truncating the level of asymmetry information. Using the data from two different countries, Indonesia (Asia) and Portugal (Europe), we extracted 37 companies with time period of observation ranges from 2012 to 2016. To manifest the empirical test, we use CSR report (CSR_Rep), CSR committee (CSR_com), CSR assurance (CSR_ass) and GRI adoption as the proxies of CSR practice, while the proxies of ESG performance are represented by Environmental (ENVscr), Social (SOCscr), and Governance (GOVscr) pillar scores as obtained from Thomson Reuters ASSET4 database. Bid-ask spread is used as the surrogate indicator of asymmetry information. The empirical test reveals that only variable GRI and SOCscr show negative and significant association with bid-ask spread. Whilst, the remaining variables of CSR practice (CSR_rep, CSR_com, CSR_ass), and ESG performance (ENVscr and GOVscr) are negatively associated with asymmetry information (Spread) but statistically insignificant. Our results suggest that CSR practice and ESG performance are weakly associated with asymmetry information, in which most of CSR practices and ESG performance need a time lag to allow them to be value relevant information in mitigating the level of asymmetry information.